Lactose Induces Phenotypic and Functional Changes of Neutrophils and Macrophages to Alleviate Acute Pancreatitis in Mice - Pan, Li-Long; Deng, Yuan-Yuan; Wang, Ruxing; Wu, Chengfei; Li, Jiahong; Niu, Wenying; Yang, Qin; Bhatia, Madhav; Gudmundsson, Gudmundur H.; Agerberth, Birgitta; Diana, Julien; Sun, Jia (Frontiers in Immunology, 2018)
Acute pancreatitis (AP) is one common clinical acute abdominal disease, for which specific pharmacological or nutritional therapies remain elusive. Lactose, a macronutrient and inducer of innate immune defense responses, possesses immune modulatory functions. The current study aimed to investigate potential modulatory effects of lactose and interplay between the nutrient and pancreatic immunity during experimentally induced AP in mice. We found that either prophylactic or therapeutic treatment of lactose time-dependently reduced the severity of AP, as evidenced by reduced pancreatic edema, serum amylase levels and pancreatic myeloperoxidase activity as well as by histological examination of pancreatic damage. Overall, lactose promoted a regulatory cytokine milieu in the pancreas and reduced the infiltration by inflammatory neutrophils and macrophages. On acinar cells, lactose was able to suppress caerulein-induced inflammatory signaling pathways and to suppress chemoattractant TNF-α and MCP-1 production. Additionally, lactose acted on pancreas-infiltrated macrophages increasing their production of IL-10 while decreasing TNF-α production. Notably, lactose treatment reversed AP-associated infiltration of activated neutrophils. Lastly, the effect of lactose on neutrophil infiltration was mimicked by a galectin-3 antagonist, suggesting a potential endogenous target of lactose. Together, the current study demonstrates an immune regulatory effect of lactose to alleviate AP and suggests its potential as a convenient, value-added therapeutic macronutrient to treat AP and lower the risk of its systemic complications.